Implementation Of Inclusive Education For ADHD Children In Regular Elementary School - Mutiara Putri, Sheryl; Kurnia, Budi; Supena, Asep; Bintoro, Totok (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2025)
Regular elementary schools without an inclusion label are still required to accept students with special needs, including ADHD. This study aims to identify the teaching processes implemented by teachers for ADHD students in regular schools without special education assistants. The research was conducted at a public elementary school in Sukabumi City in November 2024. The method used was descriptive with a qualitative approach. Data were collected through an ADHD identification instrument, in-depth interviews with the classroom teacher, and learning documentation. The research subjects consisted of one classroom teacher and a first-grade student suspected of having ADHD. The findings indicate that the student only met three out of 17 ADHD indicators. This was due to limited teacher observations or insufficient supporting information. In the learning process, the teacher applied strategies such as behavior management, group work, seat arrangement, giving instructions, and managing tantrums, all tailored to the student's needs. However, services for ADHD students in regular schools remain limited. Therefore, further efforts are needed from teachers and schools to enhance support, including collaboration with parents and specialists. This study is expected to serve as a reference for developing inclusive education practices in regular schools.